The Second Wave of Post-Soviet Criminal Procedural Codifications: First Results - Golovko, L. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The author analyzes the phenomenon of the second wave of post-Soviet criminal procedural codifications, its specific features which are not always within the logic of the classic doctrine of codification, as well as the first practical results of these codifications, that are not satisfactory. The author tries to comprehend the reasons of this phenomenon.